Facile-fabricated foamed geopolymer sphere for heavy metal removal from wastewater / Tan Tee How ... [et al.] - Tan, Tee How; Mo, Kim Hung; Lai, Sai Hin; Ling, Tung-Chai (2021)
Due to the high discharging of untreated wastewater into the environment, heavy metal pollution has been at scrutiny, and the impacts are tremendous to the environment and living organism. Therefore, it is vital to decontaminate the wastewater to prevent further ill impacts. In this work, a facile-fabricated foamed geopolymer sphere has been investigated for its heavy metal removal performance. Four different heavy metals had been selected, which were lead (Pb), cadmium (Cd), copper (Cu) and nickel (Ni). The foamed geopolymer sphere was synthesized via a simple direct-moulding method . After foaming, the density and strength of the foamed geopolymer sphere was reduced from 1810 kg/m3 to 980 kg/m3, and from 2.2 MPa to 0.7 MPa, respectively. The foamed geopolymer sphere was able to maintain its integrity after the adsorption testing, proving that 0.7 MPa strength was sufficient. On the other hand, the heavy metal removal performance of foamed geopolymer sphere was increased substantially compared to the non-foamed geopolymer sphere. Results demonstrate that the Pb(II), Cd(II), Ni(II), and Cu(II) removal capacity of foamed geopolymer sphere was 26.77 mg/g, 26.14 mg/g, 24.69 mg/g, and 21.46, respectively, which was approximately 3-6 times increment compared to non-foamed geopolymer sphere. This improvement is attributed to the enhancement of the specific surface area and porosity of the geopolymer sphere after foaming, which subsequently improve the adsorption capacity. Furthermore, the foamed geopolymer sphere can be retrieved easily upon exhausted, which simplifies the adsorption process.